High prevalence of stress fractures and long-term amenorrhoea in high endurance female athletes: The misleading lack of correlation with bone mineral density - García-Alonso, M.; Corral-Gudino, L. (Journal of Orthopaedics, 2024)
Aim & objectives Females who engage in high levels of sports have a high prevalence of menstrual cycle disorders and bone stress injuries (BSI). In this study, we determined the prevalence of menstrual disorders and fractures in female athletes and their association with bone mineral density (BMD) parameters.